Practical and facile approach towards indole alkaloids: (-)-mitralactonine - Chavan, Subhash P.; Sharma, Pallavi; Sivappa, Rasapalli; Kalkote, Uttam R. (Synlett, 2007)
An efficient approach to (-)-mitralactonine using Pictet-Spengler cyclisation with a highly functionalised masked aldehyde is described. Sharpless asymmetric dihydroxylation (SAD) is utilised to introduce chirality in the key substrate.
Keywords: alkaloids; asymmetric; cyclisations; dihydroxylations; thioacetats

Rh(II)-catalyzed intramolecular N-H insertion of D-glucose-derived delta-amino alpha-diazo beta-ketoester: Synthesis of pyrrolidine iminosugars - Vyavahare, Vinod P.; Chattopadhyay, Subrata; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2007)
The rhodium acetate catalyzed reaction of D-glucose-derived delta-amino alpha-diazo beta-ketoester allows a stereoselective beta-facial intramolecular N-H insertion reaction that leads to formation of the bicyclic pyrrolidinone ring skeleton in high yield. The sugar-substituted pyrrolidinone thus obtained was elaborated to allow the synthesis of promising glycosidase inhibitors, namely, 2,5-dideoxy2,5-imino-L-glycero-alpha-D-galactoheptitol and 2,5-dideoxy-2,5-imino-D-galactitol.
Keywords: alkaloids; azasugars; carbohydrates; N-H insertion; Pyrrolidines; rhodium carbenoid

Total synthesis of (+)-camptothecin via an intramolecular palladium-catalyzed cyclization strategy - Chavan, Subhash P.; Pathak, Ashok B.; Kalkote, Uttam R. (Synlett, 2007)
The novel cascade intramolecular Pd-catalyzed cyclization followed by aromatization for the construction Of D ring of (+)-camptothecin as a key step is demonstrated.
Keywords: alkaloids; antitumor; cyclizations; Natural products; Palladium

Tandem aza-michael-condensation-aldol cyclization reaction: approach to the construction of DE synthon of (+/-)-camptothecin - Chavan, Subhash P.; Dhawane, Abasaheb N.; Kalkote, Uttam R. (Synlett, 2008)
An efficient synthesis of the DE ring of camptothecin, employing a Reformatsky and a tandem one-pot, three-step transformation involving aza-Michael reaction, condensation with ethyl malonyl chloride followed by intramolecular `aldol' reaction to furnish the dihydropyridone derivative from commercially available starting materials, has been achieved.
Keywords: Aldol cyclizations; alkaloids; antitumor; Natural products; Reformatsky reaction

Facile synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone - Upadhyay, Puspesh K.; Prasad, Rajendra; Pandey, Menaka; Kumar, Pradeep (Tetrahedron Letters, 2009)
A short synthesis of 5,6-dihydro-5-hydroxy-2(1H)-pyridone was achieved from L-serine employing Horner-Emmons olefination as the key step. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Horner-Emmons olefination; L-serine; Pyridone; Z-selectivity

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Construction of the 5,10b-phenanthridine skeleton using [3+2]-cycloaddition of a non-stabilized azomethine ylide: total synthesis of (+/-)-maritidine and (+/-)-crinine alkaloids - Pandey, Ganesh; Gupta, Nishant R.; Gadre, Smita R. (European Journal of Organic Chemistry, 2011)
Vicinal quaternary and tertiary stereocenters of the 5,10b-phenanthridine skeleton 1 are constructed simultaneously in one step by the [3+2]-cycloaddition of non-stabilized azomethine ylide 9, generated by sequential double desilylation of 10 utilizing silver(I) fluoride as a one-electron oxidant. The regioas well as stereochemical origin of this cycloaddition reaction is explained through a favorable transition state 9''. The strategy is successfully applied for the total synthesis of the biologically active alkaloids (+/-)-maritidine (1a), (+/-)-crinine (1b), and their analogues (1d, 1e, and 1f).
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Natural products; Ylides

One-step stereospecific strategy for the construction of the core structure of the 5,11-methanomorphanthridine alkaloids in racemic as well as in optically pure form: synthesis of (+/-)-pancracine and (+/-)-brunsvigine - Pandey, Ganesh; Kumar, Ravindra; Banerjee, Prabal; Puranik, Vedavati G. (European Journal of Organic Chemistry, 2011)
The unique core structure of the complex pentacyclic 5,11-methanomorphanthridine has been constructed stereospecifically in one step by an intramolecular [3+2] cycloaddition of a non-stabilized azomethine ylide (AMY), generated by the sequential double desilylation of 14 using (AgF)-F-I as a one-electron oxidant. The formation of the single diastereomer in the key step is explained by the preferred transition state produced by endo attack of the AMY on the ``Re'' face of the dipolarophile. An asymmetric version of the cycloaddition using a chiral dipolarophile was applied to construct the core structure 68 with 63 % ee. This strategy was successfully applied to the formal synthesis of (+/-)-pancracine and the total synthesis of (+/-)-brunsvigine. An unprecedented and interesting skeletal rearrangement product 49 was observed during the attempted assembly of the E ring from 46 through Horner-Wadsworth-Emmons reactions. Mechanisms involving azetidinium salt formation or the Grob-type fragmentation are advanced to explain the observed rearrangement.
Keywords: alkaloids; Azomethine ylides; Cycloaddition; Ring-closing metathesis; synthesis design

Synthesis of C1- and C8a-epimers of (+)-castanospermine from D-glucose derived gamma,delta-epoxyazide: intramolecular 5-endo epoxide opening approach - Kalamkar, Navnath B.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2011)
A concise synthesis of two diastereomers of (+)-castanospermine namely 1- and 8a-epi-castanospermine 1b and 1c, respectively, is reported from D-glucose. The methodology involves stereoselective cross metathesis of D-glucose derived alkene 2 with 4-bromo-1-butene followed by azide displacement and m-CPBA oxidation to afford diastereomeric gamma,delta-epoxyazides 5a/5b. The Staudinger reaction of epoxyazide 5a followed by reaction with benzylchloroformate (CbzCl) unexpectedly furnished 1,3-oxazinan-2-one derivative 7 whose stereochemistry was establish by single crystal X-ray. This helps to assign the stereochemistry in the epoxidation reaction. The reduction of 5a/5b was then carried out by transfer hydrogenation to provide gamma,delta-epoxyamine that concomitantly undergoes intramolecular 5-endo-tet cyclization to afford hydroxypyrrolidine ring skeleton with sugar framework-a precursor to castanospermine analogues 1b/1c. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: alkaloids; Cross metathesis; D-Glucose; Epoxide; Oxazinanone; Polyhydroxy indolizidines

Stereoselective approach to 2,6-disubstituted piperidin-3-ol: synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline - Jha, Vishwajeet; Kauloorkar, Shruti Vandana; Kumar, Pradeep (European Journal of Organic Chemistry, 2014)
A simple and highly efficient approach to an enantioenriched 2,6-disubstituted piperidin-3-ol skeleton is developed from an aldehyde as a starting material by using organocatalytic and asymmetric dihydroxylation as the key steps. Its application to the total synthesis of (-)-deoxoprosopinine and (+)-deoxoprosophylline is also reported.
Keywords: alkaloids; Amination; Amino alcohols; synthetic methods; Wittig reactions

Synthesis of (+)-harmicine - Mondal, Pravat; N. P. Argade (Synthesis-Stuttgart, 2014)
A facile convergent access to the important indole alkaloid (+)-harmicine is described, starting from tryptamine and (R)-acetoxysuccinic anhydride via the corresponding acetoxysuccinimide in very good overall yield. Regioselective reduction of an unsymmetrical imide carbonyl group and acid-catalyzed stereoselective intramolecular cyclization were the key features involved. The directing group to induce asymmetry was finally detached via the corresponding iodide by using tributyltin hydride chemistry.
Keywords: alkaloids; cyclization; imides; reduction; stereoselective synthesis

Unified approach to fused and spirocyclic oxindoles through lewis-acid-promoted opening of spiroepoxyoxindoles with allylsilanes: application to the formal synthesis of (+/-)-physovenine - Sharma, Brijesh M.; Yadav, Mahesh; Gonnade, Rajesh G.; Kumar, Pradeep (European Journal of Organic Chemistry, 2017)
A protocol for the construction of oxindoles containing all-carbon quaternary centres in a highly regioselective manner has been developed. The reaction involves opening of spiroepoxyoxindoles with allylsilanes to give Hosomi-Sakurai-type products as well as new silicon-containing spirocyclic oxindoles. A formal synthesis of (+/-)-physovenine was accomplished in five steps using this protocol.
Keywords: alkaloids; Allylation; annulation; Lewis acids; spiro compounds

Viable alternative in vitro system and comparative metabolite profiling of different tissues for the conservation of ceropegia karulensis - Pandey, M.; Jayaramaiah, R.H.; Dholakia, B.B; Punekar, S.A.; Giri, A.P. (Plant Cell, Tissue and Organ Culture, 2017)
Abstract: Ceropegia karulensis is an endemic and critically endangered plant of the Western Ghats from India. Exploitation of the tubers and poor regeneration from seed has narrowed distribution and propagation of the species. There is a need to develop in vitro propagation methods for C. karulensis to alleviate these problems. Here, we optimized callus induction, somatic embryogenesis and microtuberization from different seedling explants viz. cotyledonary leaf and root. The environmental scanning electron microscopy was used to observe somatic embryonic origin and their developmental stages. Highest callus proliferation was recorded with 2 µM 6-benzylaminopurine and 1 µM 2,4-dichlorophenoxyacetic acid. Somatic embryos derived from cotyledonary leaf explants were more proliferative than root explants. The combination of 2 µM 6-benzylaminopurine, 2 µM naphthalene acetic acid and 7% sucrose in MS media resulted in highest microtuberization. Further, gas chromatography-mass spectrometry based metabolic profiling was carried out from native wild plants and in vitro callus tissues which identified various phytochemicals such as alkaloids, fatty acids, esters alcohols, etc. Multivariate analysis revealed the chemical disparities, where considerable variations were observed between native wild type and in vitro tissues, but no significant differences were found among in vitro callus from both root and cotyledonary explants. Overall, our results suggested that the production of various secondary metabolites found in C. karulensis was not affected by in vitro propagation and could be utilized in the conservation strategies for this plant. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: alkaloids; Metabolites

Synthesis of 2-azabicyclo[m.n.0]-alkanes and their application towards the synthesis of strychnos and stemona classes of alkaloids - Majumder, Binoy; Pandey, Ganesh (European Journal of Organic Chemistry, 2020)
2-Azabicyclo[m.n.0]alkane ring systems, the conceptual precursors towards the synthesis of Strychnos and Stemona classes of alkaloids, were synthesized from tert-butyl 2-(phenylsulfonyl)-7-aza-bicyclo[2.2.1]hept-2-ene-7-carboxylate by alkyl Grignard reaction and intramolecular cyclisation of the in situ generated ring opening product 2. The synthesized cis-hexahydroindole 3 and cis-octahydro-benzo[b]azepine 5 scaffolds were utilized to construct the advanced intermediates 25 and 35, respectively, towards the synthesis of the corresponding Strychnos and Stemona classes of alkaloids.
Keywords: alkaloids; amines; Grignard reaction; Michael addition; Natural products

Rapid bioinspired N-acyliminium ion strategy for the ABC core of the stemona alkaloids - Chavan, Subhash P.; Kalbhor, Dinesh B.; Gonnade, Rajesh G. (Asian Journal of Organic Chemistry, 2023)
A concise and highly diastereoselective bioinspired key cationic cyclization strategy for the asymmetric synthesis of the tricyclic core of the (-)-stemoamide, together with 8,9-bis-epi-stemoamide has been described. The key N-acyliminium ion precursors were accessed from L-tartaric acid and L-malic acid respectively. The use of ethyl acetoacetate derived bifunctional allylidenetriphenylphosphorane reagent in the early stage of the synthetic strategy is advantageous for the rapid construction of highly functionalized key pyrrolo[1,2-& alpha;]azepine frameworks.
Keywords: alkaloids; Biomimetic synthesis; Claisen rearrangement; cyclization; Regioselectivity

Gram-scale synthesis of (±)-tylophorine - Masal, Dattatraya P.; Reddy, D. Srinivasa (Synlett, 2025)
We report a practical scalable synthesis of the natural product (+/-)-tylophorine by using an operationally simple protecting-group-free route from readily accessible starting materials. Synthesis of a cyclic N-acetyl diester compound through cyclization, followed by two key steps (decarboxylation and a Clemmensen reduction), provides access to the target molecule.
Keywords: alkaloids; Clemmensen reduction; decarboxylation; gram-scale synthesis; tylophorine